Knowledge Management Maturity in Construction Companies. (2015) - Wibowo, Mochamad Agung; Waluyo, Rudi
Abstract: Knowledge management is a concept of managing of knowledge in the company. The implementation of concept has different levels in each company. Knowledge management maturity is a guide or measure of the company's position in managing of knowledge. The objective of the study is to identify knowledge management maturity in Indonesian construction companies. This study used a survey method and conducted by distributing questionnaires to large construction companies that implement knowledge management activities. Four level of knowledge management maturity was proposed on this study. The results show that 29 contractors at the practiced level, 20 contractors at managed level and 5 contractors at continuously improved level.